Mitochondrial replacement techniques, scientific tourism, and the global politics of science - Chan, S; Palacios‐González, C; De Jesús Medina Arellano, M (Wiley, 2017)
The United Kingdom is the first and so far only country to pass explicit legislation allowing for the licensed use of the new reproductive technology known as mitochondrial replacement therapy. The techniques used in this technology may prevent the transmission of mitochondrial DNA diseases, but they are controversial because they involve the manipulation of oocytes or embryos and the transfer of genetic material. Some commentators have even suggested that MRT constitutes germline genome modification. All eyes were on the United Kingdom as the most likely location for the first MRT birth, so it was a shock when, on September 27, 2016, an announcement went out that the first baby to result from use of the intervention had already been born. In New York City, United States‐based scientist John Zhang used maternal spindle transfer (one of the recognized MRT methods) to generate five embryos for a woman carrying oocytes with deleterious mutations of the mitochondrial DNA. Zhang then shipped the only euploid embryo to Mexico, where it was transferred to the mother's uterus. Zhang's team's travel across international borders to carry out experimental procedures represents a form of scientific tourism that has not been properly ethically explored; it can, however, have seriously detrimental effects for developing countries.